The Role of oxLDL in Intrauterine Growth Restriction and Its Relationship with Thiol Homeostasis - Layla Ali Shareef; Omeed Akbar Ali; Firas Shawqi Abdulrazzaq; Mehmet Akif Bozdayi; Rasha Raheem A. Alkarkoushi; Hasan Ulusal; Seyithan Taysi (Institute of Medico-legal Publications Pvt Ltd, 2021)
Intrauterine growth restriction(IUGR) affects about 9% of whole pregnancies.It is known that there is an increased risk of mortality and morbidity in infants.It is a serious disease that causes complications such as acute and chronic pulmonary diseases, necrotizing enterocolitis, intraventricular hemorrhage and retinopathy in the future.We aimed to study the role of oxidized low density lipoprotein (OxLDL), which is an significant risk factor in cardiovascular diseases,in IUGR and its relationship with thiol homeostasis. 38 women with IUGR and 38 healthy pregnant were included in this study.Serum total thiol and native thiol levels were analyzed with fully automatic autoanalysers in patients and controls.Serum OxLDL levels were also measured by ELISA method. According to the results of the study,it was found that OxLDL was significantly higher in the patient group compared to the control group(27.29±3.32 and 10.64±1.05 ng/mL,respectively,p <0.05).However, there was no significant difference between thiol parameters(p> 0.05).In addition, there was a negative correlation between oxLDL and native thiol and OxLDL and total thiol in the IUGR group. Oxidative stress is an important factor in the formation of OxLDL.OxLDL is an effective molecule in all stages of atherosclerosis. It appears that increased oxidative stress in IUGR patients increases OxLDL.Increased OxLDL in pregnancies complicated by IUGR may increase the risk of developing cardiovascular disease for both mother and fetus later in life.Therefore, developing treatment for OxLDL in IUGR patients may protect both mother and child from future dangers.